lili royor, minahasa, tonsea Forms of Lingual Unit in Tonsean Lyrics of Lili Royor in North Minahasa: Forms of Lingual Unit in Tonsean Lyrics of Lili Royor in North Minahasa - Katuuk, Victorien Carolina Gustaphina (IJRDO - Journal of Social Science and Humanities Research, 2020)
This research on Lili Royor dance focuses on its song lyrics, which highlight the language and culture used among Tonsea ethnicity, as reflected in their folksongs tradition. Lili Royor, one of Minahasan folksongs, has rich traditional wisdom and philosophy such as hard working, education, helping and loving each other, defending the country, respecting the elderly, and more importantly not forgetting brotherly relationship among them. The aims of this research are to find out the language forms of the lyrics contained in the Lili Royor dance. This study is a descriptive and qualitative research (Denzin, 2009:265), using linguistics approach and is based on theories by Verhaar (2001:97) and Nida (1952:60).The results show that the lyrics of Lili Royor utilize Tonsea dialect. The lingual forms in the lyrics are prefix, imperative, and particles; these repeated occurring forms are the smallest arbitrary and conventional meaningful language elements. The implied meanings of the lyrics show the highest feeling of brotherhood, which is niko manembo.The research concludes that the lyrics of Tonsea folksongs in the Lili Royor dance consist of a series of lingual elements. This research has also described the types of words by classifying, categorizing and  even by using  towards the lyrics of Lili Royor. The lyrics contain the way of thinking of the people, which has been inherited for generations among Tonsea community. The linguistics analysis through morphological, syntactic and semantic analysis used in this research has revealed the cultural implications and the way of thinking of Tonsea ethnicity.